Impact of a single nucleotide polymorphism upstream of the IL28B gene in patients positive for anti‐HCV antibody in an HCV hyperendemic area in Japan. Issue 11 (7th August 2014) - Oda, Kohei; Uto, Hirofumi; Kumagai, Kotaro; Ido, Akio; Kusumoto, Kazunori; Shimoda, Kazuya; Hayashi, Katsuhiro; Stuver, Sherri O.; Tanaka, Yasuhito; Nishida, Nao; Tokunaga, Katsushi; Tsubouchi, Hirohito
<x xml:space="preserve">Abstract</x> The influence of genetic variation at the interleukin‐28B (IL28B) locus on the natural course of hepatitis C virus (HCV) infection has not been fully investigated. The goal of this study was to examine whether an IL28B polymorphism (rs8099917) is associated with natural clearance of HCV and with disease parameters of HCV infection in an HCV hyperendemic area of Japan. The patients were 502 anti‐HCV antibody‐positive residents who participated in liver disease screening program from 2002 to 2004. Patients who underwent interferon‐based therapy or had hepatocellular carcinoma were excluded. Of these patients, 149 were negative for HCV RNA (prior infection) and 353 were positive for HCV RNA or HCV core antigen (HCV carriers). In multivariate analysis, the IL28B TT genotype was a predictor for prior HCV infection. In addition, nine of the patients with prior HCV infection were positive for anti‐HCV antibody with positive for HCV core antigen or HCV RNA before 2001, and these nine patients all had the IL28B TT genotype. Furthermore, the IL28B TT genotype was associated independently with higher HCV core antigen levels in HCV carriers. In contrast, the IL28B genotype did not affect the biochemical markers, such as alanine aminotransferase, hepatic fibrosis markers, and α‐fetoprotein, and the degree of hepatic fibrosis assessed by transient elastography in HCV carriers. We concluded that IL28B polymorphism (TT genotype) is associated with spontaneous clearance of HCV and conversely with high viral loads in HCV carriers. In contrast, the IL28B genotype does not affect disease progression such as hepatic fibrosis. J. Med. Virol. 86:1877–1885, 2014. © 2014 Wiley Periodicals, Inc.